2013
DOI: 10.1097/eja.0b013e328360bd85
|View full text |Cite
|
Sign up to set email alerts
|

Increased electrical nerve stimulation threshold of the sciatic nerve in patients with diabetic foot gangrene

Abstract: The electrical stimulation threshold for a motor response of the sciatic nerve is increased by a factor of 7.2 in patients with diabetic foot gangrene, which might hamper nerve identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
2
10
0
1
Order By: Relevance
“… 4 In patients with diabetic gangrene, stimulation thresholds were increased seven-fold compared with non-diabetic controls, again with substantial interindividual variability among diabetic patients. 9 Our findings similarly indicate that the nerve stimulation threshold in diabetic neuropathy is increased, and we confirm the large interindividual variability. In our diabetic patients, we observed a direct correlation between the duration of diabetes mellitus and the stimulation threshold for the CPN, the nerve that is typically more affected by diabetic neuropathy than the TN.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“… 4 In patients with diabetic gangrene, stimulation thresholds were increased seven-fold compared with non-diabetic controls, again with substantial interindividual variability among diabetic patients. 9 Our findings similarly indicate that the nerve stimulation threshold in diabetic neuropathy is increased, and we confirm the large interindividual variability. In our diabetic patients, we observed a direct correlation between the duration of diabetes mellitus and the stimulation threshold for the CPN, the nerve that is typically more affected by diabetic neuropathy than the TN.…”
Section: Discussionsupporting
confidence: 85%
“…Reports have shown increased stimulation thresholds for diabetic patients, including patients in which no motor response to PNS could be obtained with 2.4 mA, despite clear needle-nerve contact witnessed by ultrasound (US). 4 9 Animal data also suggest that low-threshold electrical stimulation does not protect against intraneural injection in the presence of diabetes mellitus. 10 Although nerve injury is usually followed by recovery, it remains a major concern 11 and harm can best be avoided by an approach whereby the needle does not enter the nerve.…”
mentioning
confidence: 99%
“…This prospective cohort study suggests that type‐2 diabetic patients suffering from DPN experienced a longer median time to first opioid request of more than 150%, a 50% shorter onset time for sensory and motor blockades and decreased pain scores at 24 postoperative hours. Although other authors have demonstrated an increase in minimal stimulating current during peripheral nerve blockade in diabetic patients , we were unable to replicate these results, possibly due to potential type‐2 error. Indeed, a post‐hoc analysis suggested that at least 72 patients should have been included to detect a significant difference of the same amplitude in this outcome.…”
Section: Discussionmentioning
confidence: 58%
“…Keyl et al compared diabetic patients scheduled for surgical treatment of diabetic foot gangrene and nondiabetic patients undergoing orthopedic foot or ankle surgery. 19 They observed that the geometric mean of the motor stimulation threshold of diabetic patients during popliteal nerve block was 1.9 (95% confidence interval [CI], 1.6-2.2), compared to 0.26 (95% CI, 0.-24-0.28) of non-diabetic patients, indicating an increase by a factor of 7.2. Bigeleisen et al showed that the median stimulation threshold of diabetic patients undergoing supraclavicular brachial plexus blockade was 1.3 mA, while that of non-diabetic patients was 0.5 mA.…”
Section: Diabetes Mellitus and Electrical Stimulation Thresholdmentioning
confidence: 99%